Impact of Lower Interest Rates on Bank Share Prices: The Case of Joint-stock Banks and State-controlled Banks - Fu Ziyue; Zhang Qinyao (SHS Web of Conferences)
The banking sector plays the role of an important intermediary connecting the supply and demand sides of the capital, and its stable profitability makes it an important component of dividend stocks. Changes in interest rates are a crucial factor affecting the share price of bank stocks. Against the backdrop of the current global interest rate cuts, this study aims to research the influence of interest rate changes on bank stock prices. This study collects information on share price changes and interest rate changes of eight domestic banks in China over five years from 2020 to 2024 and analyses the impact on bank stock share prices during the interest rate cut window through the event study method. It is concluded that interest rates are negatively correlated with share prices, and state-controlled banks are more significantly affected than joint-stock banks. This study investigates the relationship between interest rate changes and bank stock prices from the perspective of market securities yields, enriching the market with empirical evidence on securities price changes in the financial sector.